Basic Principles of Curriculum Development - Futihatus Sajidah Wulandari; Muliarta Abde Wilutama; Imroatul Jamila Zaen; Mohammad Yahya (Jurnal Pengabdian Nusantara, 2026)
Curriculum development is a continuous and comprehensive process aimed at creating an effective and relevant learning system that meets the needs of learners and the demands of changing times. This process involves planning and designing the curriculum by considering critical aspects such as national education goals, material relevance, flexibility in implementation, and efficient use of available resources. Fundamental principles of curriculum development include goal orientation, relevance, flexibility, continuity, and effectiveness, which serve as key guidelines in designing curricula that focus not only on academic content but also on developing broad life skills, including critical thinking, social skills, and vocational abilities. Moreover, a well-designed curriculum addresses both individual and collective differences among learners, ensures continuity across educational levels and subjects, and optimizes the use of funds, time, personnel, and facilities. The quality of curriculum development is measured based on established national education standards, with the aim of producing competent generations ready to face challenges in the workforce and society. Therefore, curriculum development grounded on these principles supports comprehensive and sustainable educational success.